Hick : the trailblazing journalist who captured Eleanor Roosevelt's heart - Miller, Sarah, 1979- (Random House Studio, 2025)
"In this riveting YA non-fiction set against the backdrop of the Great Depression, trace Lorena Hickok--or Hick's--rise from devastating childhood to renowned journalist, and watch as she forms the most significant friendship and romantic relationship of her life with first lady, Eleanor Roosevelt. Lorena Hickok came from nothing. She was on her own from the age of 14, cooking and scrubbing for one family after another as she struggled to finish school. But the girl who secretly longed for affection discovered she had a talent with words. That talent allowed Hick to carve out a place for herself in the male-dominated newsrooms of the Midwest where she earned bylines on everything from football to opera to politics. By age 35 she'd become one of the Associated Press's top reporters. At the moment her career was taking off, Hick was assigned to cover Eleanor Roosevelt during FDR's presidential campaign. By the close of 1932, Hick was head over heels in love with the wife of the president-elect. And her life would never be the same. Acclaimed author Sarah Miller read the 3500 letters that exist between Lorena Hickock and Eleanor Roosevelt to reconstruct their friendship and love, and bring Hick's story to a new generation"--Publisher's website.